THE ROLE OF HUMAN INITIATIVE ORGANIZATIONS IN FULFILLING CHILDREN'S RIGHTS IN BENGKULU - Ishak Fadlurrohim; Willya Achmad (Sosiohumaniora, 2023)
Organizations have a role in the protection of children and the fulfillment of children's rights performed individually and in groups by performing roles in accordance with well-active positions, Participative and passive. Researchers see social organizations play an important role in achieving the goals of quality of life, Basic Needs and Service Delivery. It's not out of the protection and fulfillment of a child's rights. Children become a group that has risks in every growing flower in its environment.The role of the organization both formal and informal has an important influence on creating a safe and secure environment for the child with a HOME Program and educational aid. Informant in the study involved 5 human initiative staff and 5 children has been been involved in home-program activities for two years  with School age have a family and don’t have a family. The research method used is descriptive qualitative with a purposive sampling approach through interviews and observations. Research aim to find out how the organization human initiative in protection and fulfilment of the rights of the child in bengkulu. The results The program and the activities carried out by human initiative certainly helps to actually focus on problems protection and fulfilment of the rights of children especially in providing shelter or an alternative to parenting involving a foster parent and help the accessibility of education. So the value own can give enchange his role for the community and encourage the government in creating an environment for children in bengkulu.